Leadership and Organizational Outcomes: Meta-Analysis of Empirical Studies - Karadağ, Engin (Springer, 2015)
This book focuses on the effect of leadership on organizational outcomes and summarizes the current research findings in the field. It addresses the need for inclusive and interpretive studies in the field in order to interpret leadership literature and suggest new pathways for further studies. Appropriately, a meta-analysis approach is used by the contributors to show the big picture to the researchers by analyzing and combining the findings from different independent studies. In particular, the editors compile various studies examining the relationship between the leadership and thirteen organizational outcomes separately. The philosophy behind this book is to direct future research and practices rather than addressing the limits of current studies.